Controlling Foam Stability with the Ratio of Myristic Acid to Choline Hydroxide - Arnould, Audrey (2018)
The interfacial and foam properties of a model system based on the mixture between myristic acid and choline hydroxide have been investigated as a function of the molar ratio (R) between these two components and temperature. The aim of this study was to obtain insight on the links between the self-assemblies in bulk and in the foam liquid channels, the surfactant packing at the interface, and the resulting foam properties and stability. A multiscale approach was used combining small angle neutron scattering, specular neutron reflectivity, surface tension measurements, and photography. We highlighted three regimes of foam stability in this system by modifying R: high foam stability for R < 1, intermediate at R ∼ 1, and low for R > 1. The different regimes come from the pH variations in bulk linked to R. The pH plays a crucial role at the molecular scale by setting the ionization state of the myristic acid molecules adsorbed at the gas-liquid interface, which in turn controls both the properties of the monolayer and the stability of the films separating the bubbles. The main requirement to obtain stable foams is to set the pH close to the pKa in order to have a mixture of protonated and ionized molecules giving rise to intermolecular hydrogen bonds. As a result, a dense monolayer is formed at the interface with a low surface tension. R also modifies the structure of self-assembly in bulk and therefore within the foam, but such a morphological change has only a minor effect on the foam stability. This study confirms that foam stability in surfactant systems having a carboxylic acid as polar headgroup is mainly linked to the ionization state of the molecules at the interface.